Preliminary breakdown of intracloud lightning: Initiation altitude, propagation speed, pulse train characteristics, and step length estimation. Issue 18 (17th September 2015) - Wu, Ting; Yoshida, Satoru; Akiyama, Yasuhiro; Stock, Michael; Ushio, Tomoo; Kawasaki, Zen
Abstract: Using a low‐frequency lightning location system comprising 11 sites, we located preliminary breakdown (PB) processes in 662 intracloud (IC) lightning flashes during the summer of 2013 in Osaka area of Japan. On the basis of three‐dimensional location results, we studied initiation altitude and upward propagation speed of PB processes. PB in most IC flashes has an initiation altitude that ranges from 5 to 10 km with an average of 7.8 km. Vertical speed ranges from 0.5 to 17.8 × 10 5  m/s with an average of 4.0 × 10 5  m/s. Vertical speed is closely related with initiation altitude, with IC flashes initiated at higher altitude having lower vertical speed during PB stage. Characteristics of PB pulse trains including pulse rate, pulse amplitude, and pulse width are also analyzed. The relationship between pulse rate and vertical speed has the strongest correlation, suggesting that each PB pulse corresponds to one step of the initial leader during the PB stage. Pulse rate, pulse amplitude, and pulse width all show decreasing trends with increasing initiation altitude and increasing trends with increasing vertical speed. Using a simple model, the step length of the initial leader during the PB stage is estimated. Most of initial leaders have step lengths that range from 40 to 140 m with an average of 113 m. Estimated step length has a strong correlation with initiation altitude, indicating that leaders initiated at higher altitude have longer steps. Based on the results of this study, we speculate that above certain altitude (~12 km), initial leaders in PB stages of IC flashes may only have horizontal propagations. PB processes at very high altitude may also have very weak radiation, so detecting and locating them would be relatively difficult. Key Points: Upward propagation speed in PB stage decreases with its initiation altitude PB pulse characteristics are related with vertical speed and initiation altitude Step length of initial leader in PB stage increases with initiation altitude